Enzymatic hydrolysis of Cytisus striatus: acid sulfite pretreatment optimization - Vaz, Álvaro (2019)
Ethanol production from lignocellulosic material includes three major steps: biomass pretreatment, which fragments the lignocellulosic matrix to facilitate the enzymes access to the substrate; hydrolysis, where the polysaccharides are converted into fermentable sugars (e.g. glucose and xylose) [1]; and finally, fermentation that produces ethanol or other biologically based chemicals (e.g. lactic acid, succinic acid) [2]. The aim was to study the effect of pretreatment operative variables, namely sodium bisulfite and sulfuric acid loadings, temperature and time, on released sugars in Cytisus striatus enzymatic hydrolysis with a Novozymes® cocktail. Pre-treatment intends lignin and hemicelluloses removal, reduced cellulose crystallinity and lignocellulosic network porosity increase in order to facilitate enzyme access.